Risk factors for acute myocardial infarction during the postoperative period of myocardial revascularization - Costa Jr.,José Ribamar (2003)
OBJECTIVE: To identify risk factors for acute myocardial infarction during the postoperative period after myocardial revascularization. METHODS: This was a case-control study paired for sex, age, number, type of graft used, coronary endarterectomy, type of myocardial protection, and use of extracorporeal circulation. We assessed 178 patients (89 patients in each group) undergoing myocardial revascularization, and the following variables were considered: dyslipidemia, systemic hypertension, smoking, diabetes mellitus, previous myocardial revascularization surgery, previous coronary angioplasty, and acute myocardial infarction. RESULTS: Baseline clinical characteristics did not differ in the groups, except for previous myocardial revascularization surgery, prevalent in the case group (34 patients vs. 12 patients; p = 0.0002). This was the only independent predictor of risk for acute myocardial infarction in the postoperative period, based on a multivariate logistic regression analysis (p=0.0001). Mortality and the time of hospital stay of the case group were significantly higher (19.1% vs. 1.1%; p<0.001 and 15.7 days vs. 10.6 days; p<0.05 respectively) than those of the control. CONCLUSION: Only previous myocardial revascularization was an independent predictor of acute myocardial infarction in the postoperative period, based on multivariate logistic regression analysis.